2016
DOI: 10.1007/s10967-016-5123-8
|View full text |Cite
|
Sign up to set email alerts
|

Verification measurements of the IRMM-1027 and the IAEA large-sized dried (LSD) spikes

Abstract: In the frame of the accountancy measurements of the fissile materials, reliable determinations of the plutonium and uranium content in spent nuclear fuel are required to comply with international safeguards agreements. Large-sized dried (LSD) spikes of enriched 235U and 239Pu for isotope dilution mass spectrometry (IDMS) analysis are routinely applied in reprocessing plants for this purpose. A correct characterisation of these elements is a pre-requirement for achieving high accuracy in IDMS analyses. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 14 publications
3
15
0
Order By: Relevance
“…The reason for this observation could not be found. Such a positive bias when using the Pu KRI RM2 spike, was also observed during the verification measurements of the IRMM-1027r LSD spike [37]. Nevertheless, the agreement between the gravimetric value and the IDMS results using the two different spikes was fit for purpose for a QC sample to verify the Pu amount content in the solution.…”
Section: Verification Measurements Of Qc Solutionsmentioning
confidence: 62%
See 2 more Smart Citations
“…The reason for this observation could not be found. Such a positive bias when using the Pu KRI RM2 spike, was also observed during the verification measurements of the IRMM-1027r LSD spike [37]. Nevertheless, the agreement between the gravimetric value and the IDMS results using the two different spikes was fit for purpose for a QC sample to verify the Pu amount content in the solution.…”
Section: Verification Measurements Of Qc Solutionsmentioning
confidence: 62%
“…However, with the KRI-RM-1 and -2 spikes some slight positive biases were observed in the IDMS results (Figs. 1 and 2), also when inter-linked with IRMM-1027r [37] and the most recent EQRAIN 16U. These IDMS results and spike CRMs will be part of the continuous in-house campaign on inter-linking JRC-Geel G.2′s and external spike CRMs, during which possible biases will be investigated.…”
Section: Verification Measurements Of Qc Solutionsmentioning
confidence: 90%
See 1 more Smart Citation
“…The conventional protocol was developed in our laboratory for analysis of nuclear fuel samples 3 and the values presented here are comparable with those obtained by similar analytical protocols in other nuclear laboratories. [43][44][45] We observed a very significant decrease in term of analyzed quantities (from µg to ng), liquid waste volumes (from mL to µL) and sample volumes (from µL to nL). Moreover, the time of analysis was three times shorter.…”
Section: Comparison With An Off-line Analytical Protocolmentioning
confidence: 82%
“…About 1000 units of IRMM-1027 LSD spikes are produced annually and certified in compliance with the ISO 17034 and ISO Guide 35 [14,15]. Spikes containing 235 U and 239 Pu have been successfully utilised in IDMS for safeguards inspections and in accountability measurements for operators at the reprocessing plants [9,10,[16][17][18][19][20]. The extensive use of LSD spikes over the past years has shown that IDMS, applying these spikes routinely, provides accurate results with measurement uncertainties below the target values as required by the safeguards authorities.…”
Section: Introductionmentioning
confidence: 99%